Performance analysis of beam divergence propagation through rainwater and snow pack in free space optical communication - Mustafa H. Ali; Rehab I. Ajel; Samira Abdul-kader Hussain (Institute of Advanced Engineering and Science, 2021)
In the present work the future communication requirements need to fulfill with high data rate, FSO (free space optic) with it is tremendous potential is the solution. This research observed the effectiveness analysis of FSO systems by modifying one of the most important FSO parameters beam divergence, under the most affected weather attenuating condition Rainwater and snow pack. The simulation is obtained and analyzed under single channels CSRZ-FSO (carrier-suppressed return-to-zero/free space optical) systems having capacity of 40 Gbps between two transceivers with variable distance. The connection is presently under 5 meteorological turbulences (light rain, medium rain, wet snow, heavy rain and dry snow). The results show the heavy rain and dry snow have a very high attenuation carried out in terms of Q-factor. this result led us to conclude that small divergence offers significant performance improvement for FSO link and this performance decrease every time the beam divergence increase, Therefore, to build inexpensive and reliable transmission media, we go with new method that still in the experiment area called hybrid RF/FSO (radio frequency/free space optical) that compatible with atmospherically status.